Aged Lewis rats exposed to low and moderate doses of rotenone are a good model for studying the process of protein aggregation and its effects upon central nervous system cell physiology - Michael F. Almeida; Carolliny M. Silva; Aline M. D’Unhao; Merari F. R. Ferrari (Arquivos de Neuro-Psiquiatria)
ABSTRACT Cell physiology is impaired before protein aggregation and this may be more relevant than inclusions themselves for neurodegeneration. The present study aimed to characterize an animal model to enable the analysis of the cell biology before and after protein aggregation. Ten-month-old Lewis rats were exposed either to 1 or 2 mg/kg/day of rotenone, delivered subcutaneously through mini-pumps, for one month. Hyperphosphorylated TAU, alpha-synuclein, amyloid-beta peptide and protein carbonylation (indicative of oxidative stress) were evaluated in the hippocampus, substantia nigra and locus coeruleus through immunohistochemistry or western blot. It was found that 2 mg/kg/day rotenone increased amyloid-beta peptide, hyperphosphorylation of TAU and alpha-synuclein. Rotenone at 1mg/kg/day did not alter protein levels. Protein carbonylation remained unchanged. This study demonstrated that aged Lewis rats exposed to a low dose of rotenone is a useful model to study cellular processes before protein aggregation, while the higher dose makes a good model to study the effects of protein inclusions.